A method for preparing a nanofiltration membrane and a nanofiltration membrane prepared thereby

CN117942786BActive Publication Date: 2026-10-20VONTRON TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211294917.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-21
Publication Date
2026-10-20
Estimated Expiration
2042-10-21

AI Technical Summary

Technical Problem

[0006]本发明针对现有技术中耐碱纳滤膜工业化应用过程中表现出通量低、苛性环境化学稳定性差、耐擦伤性不足等技术问题,提出了一种纳滤膜的制备方法和由其制备的纳滤膜

Benefits of technology

[0038](1)优异的耐碱性能;采用支化大分子杂臂聚胺为水相单体,氮杂苯多元苯环卤代化合物为有机相单体,界面聚合后获得纳滤膜在质量浓度为20%的氢氧化钠溶液中浸泡12周,100psi操作压力下运行20min,纳滤膜对硫酸镁脱盐率稳定在99.42%,膜通量64.6gfd。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003902287080000151
    Figure BDA0003902287080000151
  • Figure BDA0003902287080000152
    Figure BDA0003902287080000152
  • Figure BDA0003902287080000161
    Figure BDA0003902287080000161
Patent Text Reader

Abstract

The application belongs to the technical field of nanofiltration membrane manufacturing, and particularly relates to a preparation method of a nanofiltration membrane and a nanofiltration membrane prepared by the method. 10 The application takes a macromolecular polyamine as an aqueous phase monomer, plays a role of guaranteeing high selective separation stability of the alkali-resistant nanofiltration membrane, adds C2-C 10 alcohols or homologues or derivatives thereof into the aqueous phase, makes the surface of the functional layer more dense, adds a benzidine, and embeds the benzidine into a functional layer sublayer after completion of the reaction, so that the functional layer sublayer is loose and porous, and the nanofiltration membrane flux is improved; takes a nitrogenous polybenzene ring halogenated compound as an organic phase monomer, can resist damage of a harsh water environment to the membrane sheet, and endows the alkali-resistant nanofiltration membrane with excellent abrasion resistance; adds a cosolvent into the organic phase, promotes formation of a loose and porous structure of the functional sublayer; and finally uses an aldehyde aqueous solution for crosslinking treatment, so that intramolecular and intermolecular crosslinking of residual amino groups which are not completely reacted occurs, the density of the top functional layer is improved, and the nanofiltration membrane reaches bidirectional balance of the membrane flux and the desalination rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanofiltration membrane manufacturing technology, specifically relating to a method for preparing a nanofiltration membrane and a nanofiltration membrane prepared therefrom. Background Technology

[0002] Alkali-resistant nanofiltration membranes typically refer to nanofiltration membranes that exhibit operational stability and tolerance in caustic alkaline solutions with a concentration of 10%–20 wt%, such as sodium hydroxide (NaOH), potassium hydroxide (KOH), lithium hydroxide (LiOH), or organic or inorganic alkaline solutions with a pH > 12. They are mainly used in industries with complex and extreme feed liquid environments, such as viscose fiber, printing and dyeing, papermaking, food and pharmaceutical, dairy production, and precision electronics manufacturing. With the rapid development of production and daily life, the annual volume of waste alkaline solutions awaiting treatment is now very high, and the annual cumulative volume is increasing year by year. However, currently, there are relatively few commercially available alkali-resistant nanofiltration membranes, and most are prepared using amine monomers and acyl chloride monomers. The overall membrane flux is relatively low. After the membrane elements are rolled up, they require a period of special activation treatment to increase their flux and desalination rate. This results in a long production cycle, increased production costs, and significantly limited large-scale production of membrane products, severely restricting their application and development in the water treatment field.

[0003] The literature (Kah P. Lee, Jumeng Zheng, Nieck E. Benes, et al. pH stable thin film composite polyamine nanofiltration membranes by interfacial polymerisation[J]. Journal of Membrane Science, 478(2015) 75-84.) prepared an alkali-resistant nanofiltration membrane with a functional layer thickness of 400 nm by interfacial crosslinking reaction using polyethyleneimine as the aqueous phase monomer and cyanochlorotriamine as the organic phase monomer. The membrane had a MgCl2 removal rate of 96% and a flux of only 8 gfd. Its shortcomings are that the functional layer of the membrane is relatively thick and the flux is significantly low, and the abrasion resistance is insufficient. Based on this, the literature (Yang Zhang, Ying Wan, Changjiang Wu, et al. Thin-film composite nanofiltration membrane based on polyurea for extreme pH condition[J]. Journal of Membrane Science, 635(2021)119472.) adopts a new polymerization method, using hydrophilic isocyanate as the organic phase monomer, and improves the nanofiltration membrane flux by adding small molecule piperazine to the aqueous phase to regulate the thickness of the functional layer. The results show that the obtained alkali-resistant nanofiltration membrane has a functional layer thickness of 150 nm, a MgCl2 removal rate of 97%, and a flux of 13 gfd. The flux is slightly improved, but there is still a large gap to meet the high-flux industrialization needs of viscose fiber, printing and dyeing paper industry.

[0004] Existing alkali-resistant nanofiltration membranes are limited by their harsh operating conditions, resulting in a limited variety of monomers suitable for long-term alkali resistance. Furthermore, the flux of these membranes is significantly low, with mainstream commercially available alkali-resistant membranes boasting a flux of only 10-15 gfd, falling far short of the high-flux demands of industries such as viscose fiber, printing and dyeing, and papermaking. In addition, most methods for alkali recovery using nanofiltration membranes suffer from numerous problems after alkali treatment, such as increased pore size, reduced mechanical strength, and functional layer detachment with prolonged operation, severely impacting the membrane's lifespan.

[0005] Therefore, the development of nanofiltration membranes with high flux, good alkali chemical stability, strong abrasion resistance, and the ability to be continuously and scalably produced is of great practical significance in membrane material development. Summary of the Invention

[0006] This invention addresses the technical problems of low flux, poor chemical stability in harsh environments, and insufficient scratch resistance exhibited by existing alkali-resistant nanofiltration membranes in industrial applications. It proposes a method for preparing nanofiltration membranes and the nanofiltration membranes prepared therefrom.

[0007] Specifically, this is achieved through the following technical solutions:

[0008] A method for preparing a nanofiltration membrane includes the following steps:

[0009] (1) Prepare a polymer solution by taking polymer, solvent and pore-forming agent, and after preparation, degas and filter it under vacuum for later use;

[0010] (2) The polymer solution obtained by filtering in step (1) is directly scraped onto the nonwoven fabric with a scraper, immersed in water to precipitate the support layer, and the solvent is washed away to obtain a porous base membrane.

[0011] (3) The aqueous solution is uniformly applied to the surface of the porous base membrane and allowed to fully contact for 0.5 to 5 minutes. The residual solution on the surface of the porous base membrane is removed by an air knife. After the surface is air-dried, the organic phase solution is uniformly applied and allowed to fully contact for 0.5 to 5 minutes. After washing with pure water, a high-flux alkali-resistant nanofiltration membrane is obtained. The aqueous solution is composed of macromolecular polyamine, type A additive, type B additive, surfactant, acid-binding agent, and water. The mass concentration of macromolecular polyamine monomer is 0.5 to 3%, the mass concentration of type A additive is 0.1 to 1%, and the mass concentration of type B additive is 0.1 to 1%. The organic phase solution is composed of a nitrogen-containing polyphenyl ring halogenated compound, a cosolvent, and an organic solvent. The mass concentration of the nitrogen-containing polyphenyl ring halogenated compound is 0.2 to 2%, and the mass concentration of the cosolvent is 1 to 10%.

[0012] (4) The high-flux alkali-resistant nanofiltration membrane is post-treated with an aldehyde aqueous solution for 30-300s, oil is used to preserve the pores, and it is dried by blowing at 80-90℃ to form a cross-linked structure on the surface. After being treated with glycerin and then drained, the high-flux scratch-resistant and alkali-resistant nanofiltration membrane is obtained.

[0013] In step (1), the polymer is any one or a combination of two or more of polysulfone, polyethersulfone, sulfonated polyethersulfone, and polyetheretherketone; the molecular weight of the polymer is 10,000 to 100,000; the solvent is any one or a combination of two or more of N,N'-dimethylformamide, N,N'-dimethylhexamamide, and N-methylpyrrolidone; the pore-forming agent is a polymeric pore-forming agent or a small molecule pore-forming agent; the polymeric pore-forming agent is any one or a combination of two or more of polyvinylpyrrolidone, polyethylene glycol, polyethylene glycol monomethyl ether, and polyvinyl alcohol; the small molecule pore-forming agent is any one or a combination of two or more of ethanol, nano-silica, 1,4-butanediol, nano-alumina, nano-graphene, nano-titanium dioxide, carbon nanotubes, and nano-calcium oxide; the mass concentration of the polymer in the polymeric solution is 16-21%, and the mass concentration of the pore-forming agent is 1-6%.

[0014] The aqueous macromolecular polyamine monomer is any one or a combination of two or more of polyethyleneimine, polyamide-amine, polydopamine, star-shaped amine, and heteroarm-shaped amine.

[0015] The molecular weight of the polyethyleneimine is 600-6000 Da; the molecular weight of the polyamide-amine is 1000-10000 Da; the molecular weight of the polydopamine is 500-5000 Da; the star-shaped amine is any one or a combination of two or more of the following: tetra-armed polyvinyl alcohol-amine, hexa-armed polyvinyl alcohol-amine, octa-armed polyvinyl alcohol-amine, tetra-armed polyimide-amine, and hexa-armed polyimide-amine; the hetero-armed amine is any one or a combination of two or more of the following: tetra-hetero-armed azopolyethylenediamine triazine-polyamide-amine, tetra-hetero-armed azopolyethylenediamine triazine-glycidyl ether, hexa-hetero-armed ethylenediamine core polydopamine-polyethyleneimine, and octa-armed ethylenediamine core polymethacrylamide-polyethyleneimine.

[0016] The Class A additive is a fatty alcohol with 2-10 carbon atoms, or its homologues, or its derivatives; further, the Class A additive is any one or a combination of two or more of dimethyl sulfoxide, N-methylpyrrolidone, tert-butanol, ethylene glycol, pentanediol, sorbitol, and butanediol; the Class B additive is benzidine; further, the Class B additive is any one or a combination of two or more of 3,3'-dichlorobenzidine, 2,2'5,5'-tetrachlorobenzidine, 3,3'-dimethoxybenzidine, 3,3'-dihydroxybenzidine, 3,3'5,5'-tetramethylbenzidine, 3,3'-dinitrobenzidine, m,m'-dimethylbenzidine, and 5-chloro-2-nitrobenzidine.

[0017] The surfactant is sodium dodecyl sulfonate; the mass concentration of the surfactant in the aqueous solution is 0.03–0.05%.

[0018] The acid-binding agent is sodium hydroxide; the mass concentration of the acid-binding agent in the aqueous solution is 0.02-0.03%.

[0019] The aziridine polycyclic halogenated compound is an aromatic aziridine halogenated compound with 6-30 carbon atoms; further, the aziridine polycyclic halogenated compound is any one or a combination of two or more of aziridine, aziridine, aziridine anthracene, and azirphenanthrene.

[0020] The azinon is one or a combination of two or more of the isohalogenated derivatives of 1,2-dichloroazinon, 1,3-dichloroazinon, 3,5-dichloroazinon, 1,3-dichloroisoazinon, 1,4-dichloroisoazinon, 4,6-dichloroisoazinon, 3,6-dichloroisoazinon, 1,3,5-trichloroazinon, 2,3,6-trichloroazinon, 1-chloro-3-bromoazinon, 1-chloro-3,5-dibromoazinon, 1,2-dichlorodiazabenzene, 1,3-dibromodiazabenzene, 1,3,5-trichlorotriazinonzene, and 1,3,4-trichlorotriazinonzene; the azinaphthalene is 1,2-dichloroazinaphthalene, 3,5-dichloroazinaphthalene, 3,5-dichloro- 1. One or more combinations of isohalogenated derivatives of 2-diazanaphthalene, 2,4-dichloro-1,3-diazanaphthalene, 2,3-dichloro-1,4-diazanaphthalene, 1,2,7-trichlorotriazanaphthalene, 1,2,8-tribromotriazanaphthalene, 1,2,6-trichlorotriazanaphthalene, 2,4,6-trichlorotriazanaphthalene, 2,4,8-trichlorotriazanaphthalene, 1,4,9-trichlorotriazanaphthalene; wherein the azanthracene is 2,3,4-trichloroazaanthracene, 3,5,7-trichloroazaanthracene, 2,8-dichloroazaanthracene, 3,7-dichloroazaanthracene, diazaanthracene, 2,4-dichloro-1,3-diazaanthracene, 2,3-dichloro-1,4-diazaanthracene, 2,4-dichloro-1,3-diazaanthracene, 2,4 ...4-diazaanthracene, 2,4-dichloro-1,4-diazaanthracene, 2,4-dichloro-1,4-diazaanthracene, 2 The product is one or a combination of two or more isohalogenated derivatives of chloro-1,6-diazanthracene, 1,4-dichloro-2,3-diazanthracene, 3,4-dichloro-2,6-diazanthracene, 3,5,7-trichloro-2,8-diazanthracene, 1,3-dichloro-4,6-diazanthracene, and 3,6-dichloro-4,8-diazanthracene; the aziphenanthrene is 2,3,4-trichloro-1,6,10,15-tetraazanthracene, 4,8,10-trichloro-1,6,10,15-tetraazanthracene, 2,8,12-trichloro-1,6,10,15-tetraazanthracene, 2,3,6-trichloro-1,4,10,13-tetraazanthracene, 3,6,8-trichloro-1,4,10 One or more combinations of isohalogenated derivatives such as 13-tetrafluorophenanthrene, 3,8,11-trichloro-1,4,10,13-tetrafluorophenanthrene, 2,6,10-trichloro-1,4,8,15-tetrafluorophenanthrene, 3,6,12-trichloro-1,4,8,15-tetrafluorophenanthrene, 6,10,17-trichloro-1,4,8,15-tetrafluorophenanthrene, 4,6,8-trichloro-1,13,15,17-tetrafluorophenanthrene, 4,6,8-trichloro-1,13,15,17-tetrafluorophenanthrene, 4,6,8,10-tetrachloro-1,13,15,17-tetrafluorophenanthrene, and 3,6,11-trichloro-1,13,15,17-tetrafluorophenanthrene.

[0021] The co-solvent is any one or a combination of two or more of toluene, m-xylene, p-xylene, o-xylene, and 1,3,5-trimethylbenzene; the mass concentration of the organic phase co-solvent is 1-10%.

[0022] The aldehyde aqueous solution is an aliphatic dialdehyde or aromatic dialdehyde whose molecular chain contains 2-20 carbon atoms.

[0023] Furthermore, the aldehyde aqueous solution is any one or a combination of two or more of glutaraldehyde, glyoxal, succinaldehyde, o-phthalaldehyde, and pyromellitic methylformaldehyde.

[0024] The mass concentration of the aldehyde aqueous solution is 0.5% to 5%.

[0025] Another aspect of this invention relates to a nanofiltration membrane prepared according to the aforementioned method for preparing nanofiltration membranes.

[0026] The nanofiltration membrane described herein is used in the treatment of wastewater from viscose fiber production or wastewater from printing and dyeing papermaking.

[0027] Based on the environmental requirements of alkali-resistant nanofiltration membranes operating under harsh conditions, their functional layers must possess high flux, high selective separation stability, and high mechanical strength stability. Therefore, the technical principle of this invention is as follows:

[0028] 1) Using macromolecular polyamines as aqueous monomers, with high content of active functional groups and numerous crosslinking sites, effectively improves the degree of crosslinking in the polymerization reaction, ensuring the high selective separation stability of the alkali-resistant nanofiltration membrane. The high degree of branching and numerous reactive sites of the macromolecular polyamines ensure the crosslinking density of the top functional layer. If the concentration in the aqueous phase is below 0.5%, the alkali resistance stability of the formed functional layer is poor; if it is above 3%, the formed functional layer is too dense, leading to a significant decrease in membrane water production. C2-C is added to the aqueous phase. 10 Fatty alcohols or their homologues or derivatives can enhance the diffusion rate of macromolecular polyamine monomers, thus promoting their diffusion and regulating the structural morphology of the top of the functional layer, making its surface more compact. This ensures that the membrane maintains its removal rate without sacrificing flux. However, if the amount of type A additive is too low, the promoting effect will be insignificant or weak; if the amount is too high, it will adversely affect the phase reaction process, and the membrane structure will be prone to defects. Adding benzidine to the aqueous phase results in high steric hindrance, low functional group reactivity, and excellent rigidity. After the reaction, it embeds into the functional layer sublayer, making it more porous and improving the flux of the nanofiltration membrane. If the amount of benzidine added is too low, the flux improvement effect will be poor; if the amount is too high, firstly, its solubility in the aqueous phase is poor, and secondly, after embedding into the functional layer, it will form macroporous defects, causing the membrane to lose its performance.

[0029] 2) Using aza-based polycyclic benzene ring halogenated compounds as organic phase monomers, the cross-linked polymer structure formed by reacting with aqueous phase monomers has a predominantly carbon-nitrogen single bond structure. From a molecular structure design perspective, this provides sufficient alkali resistance. The aza-based polycyclic benzene rings have high rigidity, resisting damage to the membrane from harsh influent environments, thus endowing the alkali-resistant nanofiltration membrane with excellent abrasion resistance. The addition of a co-solvent to the organic phase widens the interfacial reaction region, increases monomer reaction efficiency, and further promotes the formation of a loose, porous structure in the functional sublayer.

[0030] 3) Finally, cross-linking treatment is carried out using an aldehyde aqueous solution to allow the unreacted residual amino groups to undergo intramolecular and intermolecular cross-linking, thereby increasing the density of the top functional layer and obtaining an alkali-resistant nanofiltration membrane with high selectivity, thus achieving a bidirectional balance between membrane flux and desalination rate.

[0031] The functions of each substance are as follows:

[0032] In this invention, the amount of macromolecular polyamine in the aqueous solution is strictly controlled to give full play to the high degree of branching and the many reactive sites of macromolecular polyamine, which can ensure the crosslinking density of the top functional layer. If the concentration in the aqueous phase is too low, the alkali resistance stability of the functional layer will be poor; if the amount added is too high, the functional layer will be too dense, which will lead to a significant decrease in membrane water production.

[0033] In this invention, the aqueous phase additive A can regulate the diffusion rate of the amine monomer in the aqueous phase, thus promoting its diffusion. The faster the amine monomer diffuses, the thinner and denser the functional layer formed, ensuring the membrane achieves a high removal rate without sacrificing flux. If the amount added is too low, the promoting effect will be insignificant or weak; if the amount added is too high, it will adversely affect the phase reaction process and easily lead to defects in the membrane structure.

[0034] In this invention, the aqueous additive B has the characteristics of large steric hindrance and strong molecular rigidity. After the reaction, it is embedded into the functional layer sublayer, making the sublayer more porous and thus improving the flux of the nanofiltration membrane. If the amount added is too low, the flux improvement effect will be poor; if the amount added is too high, firstly, its solubility in the aqueous phase is poor, and secondly, it will form large pore defects after being embedded in the functional layer, causing the membrane to lose its performance.

[0035] In this invention, the organic phase monomers primarily impart long-term alkali resistance and abrasion resistance to the nanofiltration membrane. If the addition amount is too low, the nanofiltration membrane will lack stability in harsh environments and its abrasion resistance under severe conditions will also be insufficient; if the addition amount is too high, the resulting functional layer structure will be too dense, resulting in significant flux loss.

[0036] This invention uses an aqueous aldehyde solution to enhance the density of the top functional layer, achieving a bidirectional balance between membrane flux and desalination rate. If the amount added is too low, the post-treatment effect will be poor and the desalination rate will be low. If the amount added is too high, the remaining post-treatment solution will remain on the membrane surface, which will appear as irregular yellow or dark yellow areas after air drying, significantly affecting the appearance of the membrane.

[0037] Beneficial effects:

[0038] (1) Excellent alkali resistance; branched macromolecular heterocyclic polyamine is used as the aqueous phase monomer and azirbenzene polycyclic halogenated compound is used as the organic phase monomer. After interfacial polymerization, the nanofiltration membrane is immersed in a 20% sodium hydroxide solution for 12 weeks and operated at 100psi operating pressure for 20 min. The desalination rate of magnesium sulfate of the nanofiltration membrane is stable at 99.42% and the membrane flux is 64.6 gfd.

[0039] (2) High membrane flux performance: When the amount of polyethylene glycol monomethyl ether added is 2%, the amount of benzidine added is 0.1%, and the amount of cosolvent added is 3%, the alkali-resistant nanofiltration membrane reaches a membrane flux of 66.4 gfd after running for 20 minutes at an operating pressure of 100 psi.

[0040] (3) Excellent selective separation performance; using aromatic aldehydes or aliphatic aldehydes as crosslinking agents, the unreacted residual amino groups can undergo further intramolecular and intermolecular crosslinking under conditions of 80-90℃, thereby improving the desalination rate of the alkali-resistant nanofiltration membrane. When the concentration of pyromellitic aldehyde is 4%, the reaction temperature is 90℃, and the post-treatment time is 180s, the desalination rate of the obtained nanofiltration membrane reaches up to 99.72%.

[0041] (4) Excellent scratch resistance; The nanofiltration membrane prepared by this invention has high surface strength modulus and excellent scratch resistance. The functional layer has undergone six repeated scratch tests. After dyeing, the surface remains unstained. The desalination rate and flux remain stable, with a flux of 63.8 gfd and a desalination rate of 99.60%. Detailed Implementation

[0042] The specific embodiments of the present invention will be described in further detail below, but the present invention is not limited to these embodiments. Any improvements or substitutions based on the basic spirit of these embodiments shall still fall within the scope of protection claimed by the claims of the present invention.

[0043] Example 1

[0044] A method for preparing a nanofiltration membrane includes the following steps:

[0045] Step 1: Preliminary Preparation

[0046] (1) The polymer solution is composed of the following mass fractions of substances: 16% polysulfone, 2% polyethylene glycol monomethyl ether, and the balance is N,N'-dimethylformamide, which is obtained by heating and dissolving.

[0047] (2) The aqueous solution is composed of the following substances by mass fraction: 0.5% polyethyleneimine, 0.2% sorbitol, 0.1% 3,3'-dichlorobenzidine, 0.03% sodium dodecyl sulfonate, 0.02% sodium hydroxide, and the balance is water;

[0048] (3) The organic phase solution is composed of the following substances by mass fraction: 0.2% 1,2-dichlorodiazabenzene, 3% m-xylene, and the balance is n-hexane;

[0049] The second step is to fabricate the nanofiltration membrane.

[0050] (4) Prepare a polymer solution according to the formula amount, heat and dissolve the polymer solution, vacuum degas it, cool it, scrape it onto a non-woven fabric with a certain thickness, immerse it in water to precipitate the support layer, and wash away the solvent with pure water to obtain a polysulfone porous base membrane.

[0051] (5) Prepare an aqueous solution according to the formula, apply the aqueous solution evenly to the surface of the polysulfone porous base membrane, make full contact for 2 minutes, then remove the residual solution on the membrane surface by air knife, and allow it to dry completely.

[0052] (6) Prepare the organic phase solution according to the formula amount, apply the organic phase solution evenly to the surface of the membrane obtained in step (5), make full contact for 2 minutes, and blow dry with a fan;

[0053] (7) The membrane from step (6) is immersed in a 0.5% glyoxal aqueous solution for 30 seconds, dried at 80°C with a hot air blower, and drained after passing through glycerin to obtain a nanofiltration membrane.

[0054] Example 2

[0055] A method for preparing a nanofiltration membrane includes the following steps:

[0056] Step 1: Preliminary Preparation

[0057] (1) The polymer solution is composed of the following substances in mass fraction: 17% polysulfone, 2% polyethylene glycol 400, and the balance is N,N'-dimethylformamide, which is obtained by heating and dissolving.

[0058] (2) The aqueous solution is composed of the following substances by mass fraction: 1.0% star-shaped six-armed polyvinyl alcohol-amine, 0.3% dimethyl sulfoxide, 0.2% 3,3',4,4'-tetrachlorobenzidine, 0.03% sodium dodecyl sulfonate, 0.02% sodium hydroxide, and the balance is water;

[0059] (3) The organic phase solution is composed of the following substances by mass fraction: 0.4% 2,4,6-trichlorotriazanaphthalene, 4% o-xylene, and the balance is n-hexane;

[0060] The second step is to fabricate the nanofiltration membrane.

[0061] (4) Prepare a polymer solution according to the formula amount, heat and dissolve the polymer solution, degas it under vacuum, cool it, scrape it onto a non-woven fabric with a scraper to a certain thickness, immerse it in water to precipitate the support layer, and wash away the solvent with pure water to obtain a polysulfone porous base membrane.

[0062] (5) Prepare an aqueous solution according to the formula, apply the aqueous solution evenly to the surface of the polysulfone porous base membrane, make full contact for 2 minutes, then remove the residual solution on the membrane surface by air knife, and allow it to dry completely.

[0063] (6) Prepare the organic phase solution according to the formula amount, apply the organic phase solution evenly to the surface of the membrane obtained in step (5), make full contact for 2 minutes, and blow dry with a fan;

[0064] (7) The membrane from step (6) is immersed in a 1.0% glutaraldehyde aqueous solution for 60 seconds, dried at 80°C with a hot air blower, and drained after passing through glycerol to obtain a nanofiltration membrane.

[0065] Example 3

[0066] A method for preparing a nanofiltration membrane includes the following steps:

[0067] Step 1: Preliminary Preparation

[0068] (1) The polymer solution is composed of the following substances in mass fraction: 18% polyethersulfone, 3% polyethylene glycol 600, and the balance is N,N'-dimethylformamide, which is obtained by heating and dissolving.

[0069] (2) The aqueous solution is composed of the following substances by mass fraction: 1.5% star-shaped hexahedral ethylenediamine nucleus polydopamine-polyethyleneimine, 0.5% N-methylpyrrolidone (K15), 0.3% 3,3'-dimethoxybenzidine, 0.05% sodium dodecyl sulfonate, 0.02% sodium hydroxide, and the balance is water;

[0070] (3) The organic phase solution is composed of the following substances by mass fraction: 0.6% 3,5,7-trichloro-2,8-diazathane, 5% p-xylene, and the balance is n-hexane;

[0071] The second step is to fabricate the nanofiltration membrane.

[0072] (4) Prepare a polymer solution according to the formula amount, heat and dissolve the polymer solution, vacuum degas it, cool it, scrape it onto a non-woven fabric with a scraper to a certain thickness, immerse it in water to precipitate the support layer, and wash away the solvent with pure water to obtain a porous base film.

[0073] (5) Prepare an aqueous solution according to the formula, apply the aqueous solution evenly to the surface of the porous base membrane, make full contact for 2 minutes, then remove the residual solution on the membrane surface by air knife, and allow it to dry completely.

[0074] (6) Prepare the organic phase solution according to the formula amount, apply the organic phase solution evenly to the surface of the membrane obtained in step (5), make full contact for 2 minutes, and blow dry with a fan;

[0075] (7) The membrane from step (6) is immersed in a 2.0% succinate aqueous solution for 90 seconds, dried at 85°C with a hot air blower, and drained after passing through glycerol to obtain a nanofiltration membrane.

[0076] Example 4

[0077] A method for preparing a nanofiltration membrane includes the following steps:

[0078] Step 1: Preliminary Preparation

[0079] (1) The polymer solution is composed of the following substances in mass fraction: 19% sulfonated polyethersulfone, 4% polyethylene glycol 1000, and the balance is N,N'-dimethylformamide, which is obtained by heating and dissolving.

[0080] (2) The aqueous solution is composed of the following substances by mass fraction: 2.0% polyamide-amine (molecular weight 3000), 0.6% N-methylpyrrolidone (k30), 0.5% 3,3'-dihydroxybenzidine, 0.05% sodium dodecyl sulfonate, 0.03% sodium hydroxide, and the balance is water;

[0081] (3) The organic phase solution is composed of the following substances by mass fraction: 0.8% 3,4-dichloro-2,6-diazathane, 7% p-xylene, and the balance is n-hexane;

[0082] The second step is to fabricate the nanofiltration membrane.

[0083] (4) Prepare a polymer solution according to the formula amount, heat and dissolve the polymer solution, vacuum degas it, cool it, scrape it onto a non-woven fabric with a scraper to a certain thickness, immerse it in water to precipitate the support layer, and wash away the solvent with pure water to obtain a porous base film.

[0084] (5) Prepare an aqueous solution according to the formula, apply the aqueous solution evenly to the surface of the porous base membrane, make full contact for 2 minutes, then remove the residual solution on the membrane surface by air knife, and allow it to dry completely.

[0085] (6) Prepare the organic phase solution according to the formula amount, apply the organic phase solution evenly to the surface of the membrane obtained in step (5), make full contact for 2 minutes, and blow dry with a fan;

[0086] (7) The membrane from step (6) is immersed in a 3.0% phthalaldehyde aqueous solution for 120 seconds, dried at 85°C with a hot air blower, and drained after passing through glycerol to obtain a nanofiltration membrane.

[0087] Example 5

[0088] A method for preparing a nanofiltration membrane includes the following steps:

[0089] Step 1: Preliminary Preparation

[0090] (1) The polymer solution is composed of the following mass fractions of substances: 20% polyether ether ketone, 6% ethanol, and the balance is N,N'-dimethylformamide, which is obtained by heating and dissolving.

[0091] (2) The aqueous solution is composed of the following substances by mass fraction: 3.0% tetra-armed polyvinyl alcohol-amine (molecular weight 4000), 0.8% butanediol, 0.8% 2,2',5,5'-tetrachlorobenzidine, 0.05% sodium dodecyl sulfonate, 0.03% sodium hydroxide, and the balance is water;

[0092] (3) The organic phase solution is composed of the following substances by mass fraction: 1.2% 2,3,4-trichloro-1,6,10,15-tetrafluoroethylene, 8% p-xylene, and the balance is n-hexane;

[0093] The second step is to fabricate the nanofiltration membrane.

[0094] (4) Prepare a polymer solution according to the formula amount, heat and dissolve the polymer solution, vacuum degas it, cool it, scrape it onto a non-woven fabric with a scraper to a certain thickness, immerse it in water to precipitate the support layer, and wash away the solvent with pure water to obtain a porous base film.

[0095] (5) Prepare an aqueous solution according to the formula, apply the aqueous solution evenly to the surface of the polysulfone porous base membrane, make full contact for 2 minutes, then remove the residual solution on the membrane surface by air knife, and allow it to dry completely.

[0096] (6) Prepare the organic phase solution according to the formula amount, apply the organic phase solution evenly to the surface of the membrane obtained in step (5), make full contact for 2 minutes, and blow dry with a fan;

[0097] (7) The membrane from step (6) is immersed in a 4.0% aqueous solution of pyromellitic aldehyde for 180 seconds, dried at 90°C with a hot air blower, and drained after passing through glycerol to obtain a nanofiltration membrane.

[0098] Under the test conditions of operating pressure 100 psi, feed water magnesium sulfate 2000 ppm, operating time 20 min, and feed water temperature 25℃, the nanofiltration membrane performance of each group of examples is shown in Table 1; comparative examples were also set up as follows:

[0099] Comparative Example

[0100] A method for preparing a nanofiltration membrane includes the following steps:

[0101] Step 1: Preliminary Preparation

[0102] (1) The polymer solution is composed of the following mass fractions of substances: 16% polysulfone, 2% polyethylene glycol monomethyl ether, and the balance is N,N'-dimethylformamide, which is obtained by heating and dissolving.

[0103] (2) The aqueous solution is composed of the following substances by mass fraction: 0.5% polyethyleneimine, 0.03% sodium dodecyl sulfonate, 0.02% sodium hydroxide, and the remainder is water;

[0104] (3) The organic phase solution is composed of the following substances by mass fraction: 0.2% 1,2-dichlorodiazabenzene, with the balance being n-hexane;

[0105] The second step is to fabricate the nanofiltration membrane.

[0106] (4) Prepare a polymer solution according to the formula amount, heat and dissolve the polymer solution, vacuum degas it, cool it, scrape it onto a non-woven fabric with a certain thickness, immerse it in water to precipitate the support layer, and wash away the solvent with pure water to obtain a polysulfone porous base membrane.

[0107] (5) Prepare an aqueous solution according to the formula, apply the aqueous solution evenly to the surface of the polysulfone porous base membrane, make full contact for 2 minutes, then remove the residual solution on the membrane surface by air knife, and allow it to dry completely.

[0108] (6) Prepare the organic phase solution according to the formula amount, apply the organic phase solution evenly to the surface of the membrane obtained in step (5), make full contact for 2 minutes, and blow dry with a fan;

[0109] (7) The membrane from step (6) is rinsed with pure water for 30 seconds, dried with a hot air blower at 80°C, and then drained after passing through glycerin to obtain a nanofiltration membrane.

[0110] Table 1 Magnesium sulfate removal rate and flux of nanofiltration membranes in each group of examples

[0111]

[0112] The nanofiltration membrane obtained in Example 5 was subjected to a long-term alkali resistance evaluation, and the results are shown in Table 2.

[0113] Table 2. Long-term evaluation of alkali resistance (12 weeks)

[0114] 0 99.72 62.3 2 99.70 62.5 4 99.64 63.1 6 99.61 63.4 8 99.54 63.9 10 99.43 64.4 12 99.42 64.6

[0115] The nanofiltration membrane obtained in Example 5 was subjected to wiping number and performance tests, and the results are shown in Table 3.

[0116] Table 3. Number of wipes and performance test (3 back-and-forth wipes per wipe)

[0117]

[0118]

Claims

1. A method for preparing a nanofiltration membrane, characterized in that, Includes the following steps: (1) Prepare a polymer solution by taking polymer, solvent and pore-forming agent, and after preparation, degas and filter it under vacuum for later use; (2) The polymer solution obtained by filtering in step (1) is directly scraped onto the nonwoven fabric with a scraper, immersed in water to precipitate the support layer, and the solvent is washed away to obtain a porous base membrane. (3) The aqueous solution is uniformly applied to the surface of the porous base membrane and allowed to fully contact for 0.5 to 5 minutes. The residual solution on the surface of the porous base membrane is removed by an air knife. After the surface is air-dried, the organic phase solution is uniformly applied and allowed to fully contact for 0.5 to 5 minutes. After washing with pure water, a high-flux alkali-resistant nanofiltration membrane is obtained. The aqueous solution is composed of macromolecular polyamine, type A additive, type B additive, surfactant, acid-binding agent, and water. The organic phase solution is composed of nitrogen-containing polycyclic benzene ring halogenated compound, co-solvent, and organic solvent. (4) The high-flux alkali-resistant nanofiltration membrane is post-treated with an aldehyde aqueous solution for 30-300s, dried in a forced air at 80-90℃, soaked in glycerol and then drained to obtain a high-flux scratch-resistant alkali-resistant nanofiltration membrane. In step (1), the polymer is any one or a combination of two or more of polysulfone, polyethersulfone, sulfonated polyethersulfone, and polyetheretherketone; The macromolecular polyamine monomer in the aqueous phase is any one or a combination of two or more of polyethyleneimine, polyamide-amine, polydopamine, star-shaped amine, and heteroarm-shaped amine. The Class A additive is any one or a combination of two or more of dimethyl sulfoxide, N-methylpyrrolidone, tert-butanol, ethylene glycol, pentanediol, sorbitol, and butanediol; the Class B additive is any one or a combination of two or more of 3,3'-dichlorobenzidine, 2,2',5,5'-tetrachlorobenzidine, 3,3'-dimethoxybenzidine, 3,3'-dihydroxybenzidine, 3,3',5,5'-tetramethylbenzidine, 3,3'-dinitrobenzidine, and 5-chloro-2-nitrobenzidine. The aza-based polybenzene ring halogenated compounds are any one or a combination of two or more of the following: azabenzene halogenated compounds, azanaphthalene halogenated compounds, azaanthracene halogenated compounds, and azaphenanthrene halogenated compounds; The aldehydes in the aqueous aldehyde solution are aliphatic or aromatic dialdehydes whose molecular chains contain 2-20 carbon atoms.

2. The method for preparing a nanofiltration membrane as described in claim 1, characterized in that, The polymer has a molecular weight of 10,000 to 100,000; the solvent is any one or a combination of two or more of N,N'-dimethylformamide, N,N'-dimethylhexamamide, and N-methylpyrrolidone; the pore-forming agent is a high-molecular-weight pore-forming agent or a low-molecular-weight pore-forming agent; the high-molecular-weight pore-forming agent is any one or a combination of two or more of polyvinylpyrrolidone, polyethylene glycol, polyethylene glycol monomethyl ether, and polyvinyl alcohol; the low-molecular-weight pore-forming agent is any one or a combination of two or more of ethanol, nano-silica, 1,4-butanediol, nano-alumina, nano-graphene, nano-titanium dioxide, carbon nanotubes, and nano-calcium oxide; the polymer mass concentration in the polymer solution is 16-21%, and the pore-forming agent mass concentration is 1-6%.

3. The method for preparing a nanofiltration membrane as described in claim 1, characterized in that, The aqueous solution contains 0.5–3% macromolecular polyamine monomers, 0.1–1% of type A additives, and 0.1–1% of type B additives.

4. The method for preparing a nanofiltration membrane as described in claim 1, characterized in that, The molecular weight of the polyethyleneimine is 600-6000 Da; the molecular weight of the polyamide-amine is 1000-10000 Da; the molecular weight of the polydopamine is 500-5000 Da; the star-shaped amine is any one or a combination of two or more of the following: tetra-armed polyvinyl alcohol-amine, hexa-armed polyvinyl alcohol-amine, octa-armed polyvinyl alcohol-amine, tetra-armed polyimide-amine, and hexa-armed polyimide-amine; the hetero-armed amine is any one or a combination of two or more of the following: tetra-hetero-armed azopolyethylenediamine triazine-polyamide-amine, tetra-hetero-armed azopolyethylenediamine triazine-glycidyl ether, hexa-hetero-armed ethylenediamine core polydopamine-polyethyleneimine, and octa-armed ethylenediamine core polymethacrylamide-polyethyleneimine.

5. The method for preparing a nanofiltration membrane as described in claim 1, characterized in that, The organic phase solution contains 0.2-2% by mass of nitrogen-containing polycyclic benzene ring halogenated compounds, and the cosolvent contains 1-10% by mass.

6. The method for preparing a nanofiltration membrane as described in claim 1, characterized in that, The mass concentration of the co-solvent is 1-10%.

7. The method for preparing a nanofiltration membrane as described in claim 1, characterized in that, The mass concentration of the aldehyde aqueous solution is 0.5% to 5%.

8. A nanofiltration membrane prepared by any one of claims 1-7.

Citation Information

Patent Citations

  • Polyamide composite nanofiltration membrane and preparation method thereof

    CN114130206A

  • Amino-siloxane FLUX enhancing agent for improving composite polyamide reverse|osmosis membrane performance

    WO2014031271A1